The Impact of E-Service Quality (E-SQ) towards Repurchase Intention Mediated by Customer Satisfaction in the Context of Millennial Users of Online Travel Agencies (OTA): Learning from the Case of Traveloka in Indonesia - Cindy Karina (iBuss Management, 2019)
Scholars argue that for an e-service based organization like OTA, what determines a customer satisfaction that can lead to a repurchase intention is E-SQ, especially for millennials customers. Traveloka is one of Indonesia’s OTA who is at the risk of losing its customers. Therefore, it is important for Traveloka to improve its E-SQ to gain a stronger repurchase intention. Correspondingly, this study aims to know whether E-SQ elements of Traveloka influence repurchase intention. Furthermore, this study would like to know whether satisfaction mediates the relationship between E-SQ elements and repurchase intention. The researcher adopts six E-SQ elements proposed by Park, Gretzel, & Turk, (2007), namely: ease of use, information-content, security-privacy, visual appeal, fulfillment, and responsiveness.This study gathers data through online questionnaire. Furthermore, this study uses simple random sampling as the sampling design, in which the sample will be taken randomly from the target population. The data then is analyzed using Multiple Linear Regression with Path Analysis and Sobel Test. The findings shows that E-SQ elements significantly influence millennials’ repurchase intention, except for visual appeal. Furthermore, the findings show that customer satisfaction gives mediation effect on the relationship of ease of use, security-privacy, and fulfillment towards repurchase intention. Keywords: E-SQ, customer satisfaction, repurchase intention, Traveloka, millennials